The Role of Social Media in the Spread of Religious Extremism and its Impact on Social Pathology - Anggun Annisa Imammi; Rahmat Saputra (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2024)
Social media has played an increasingly significant role in facilitating the spread of religious extremism. This research aims to investigate the role of social media in the spread of religious extremism and its impact on social pathology. The research method used is a qualitative method with a library research approach and involves social media content analysis. The results of this research reveal patterns of the spread of religious extremist thought through social media, its impact on individual attitudes, and its implications for social pathology. A better understanding of these dynamics is crucial in efforts to address the spread of religious extremism and its impact on social pathology. The results of this research provide a strong basis for designing more effective prevention strategies and mitigation efforts in dealing with this phenomenon in the ever-growing digital era.